PENGARUH PEMBELAJARAN PENDIDIKAN AGAMA ISLAM TERHADAP PERILAKU SISWA - Fitri Maulida; Suprapto Suprapto (Fakultas Agama Islam Universitas Muhammadiyah Luwuk, 2023)
Islamic Religious Education has an important influence on the behavior and morals of students, so that schools, teachers and parents have a role in providing facilities to support the quality of good behavior and morals. However, in general-based schools such as SMAN there are students who behave less well due to the lack of moral inculcation given so that there is a need to increase religious learning. This study aims to analyze Islamic religious learning in terms of student behavior and measure Islamic religious learning that influences student behavior. The method in this research is to use Analytical Descriptive by describing and providing an overview of a research object through collected data or samples. The data is in the form of quantitative data or data that shows results in the form of numbers while the data collection techniques used are in the form of observation, questionnaires, and documentation. The results of the study show that learning Islamic Religious Education has a significant influence on the behavior of students at Pelita Tiga High School so that teachers should always provide encouragement and motivation to improve moral formation in the school environment and the community environment.